Relationship between Muscle Mass and Fasting Blood Glucose with Vascular Elasticity in Medical Students - Raja Soaloon Purba; Nurfitri Bustamam; Maria Selvester Thadeus; Marlina Dewiastuti (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Low vascular elasticity is one of the key determinants of cardiovascular disease risk. Sedentary lifestyles and high-glucose diets may decrease muscle mass and increase blood glucose levels, potentially reducing vascular elasticity. This study aimed to analyze the relationships among muscle mass, fasting blood glucose levels, and vascular elasticity in medical students. Methods: A cross-sectional study was conducted involving 53 medical students aged 18—22 years using a stratified random sampling technique. Eligible participants were non-smokers, non-alcohol consumers, and had no history of diabetes, hypertension, or the use of medications affecting blood pressure, blood glucose, or cholesterol levels. Muscle mass, fasting blood glucose, and vascular elasticity were measured using a bioelectrical impedance analyzer, capillary blood testing, and an accelerated photoplethysmograph, respectively. Data were analyzed using a Chi-square tests and multivariable Logistic Regression. Results: There were no significant differences in age, blood pressure, BMI, or eating habits between the suboptimal and normal/optimal vascular elasticity groups (p > 0.05). Multivariable analysis showed that muscle mass was significantly associated with vascular elasticity (p = 0.009; OR = 9.656; CI = 1.757–53.075), after adjustment for fasting blood glucose levels (p = 0.386; OR = 2.329; CI = 0.344–15.776). Participants with higher muscle mass were nearly 10 times more likely to have better vascular elasticity. Conclusion: Muscle mass is significantly associated with vascular elasticity in young adults, independent of fasting blood glucose levels. These findings highlight the importance of maintaining adequate muscle mass. Promoting muscle mass through healthy lifestyle habits may help preserve vascular elasticity and reduce the risk of cardiovascular disease.